Global entrepreneurship and development index - Global Entrepreneurship and Development Institute (Cheltenham Edward Elgar Publishing Ltd., 2013)
The Global Entrepreneurship and Development Index both captures the context features of entrepreneurship and fills a gap in the measurement of development. Building on recent advances in entrepreneurship and economic development, the authors have created an index that offers a measure of the quality of the business formation process in 118 of the most important countries in the world.
Description based on: 2013 Latest issue consulted: 2013
Keywords: Production; ENTREPRENEURSHIP; ECONOMIC DEVELOPMENT; STATISTICS; PERIODICALS